Workload and job stress among emergency department nurses - Agus Mi'raj Darajat; Leny Triandriyana; Santi Puspitasari (JOURNAL OF Mental Health Concerns, 2026)
Background: Emergency room (ER) nurses are exposed to high workloads due to the unpredictable nature of emergency services, which may increase the risk of job stress and negatively affect nursing performance. Purpose: To examine the relationship between workload and job stress among ER nurses. Method: A quantitative study with a cross-sectional correlational design was conducted among 30 ER nurses using total sampling. Workload was assessed using the National Aeronautics and Space Administration Task Load Index (NASA-TLX), while job stress was measured using the Expanded Nursing Stress Scale (ENSS). Data were analyzed using the Spearman Rank correlation test. Results: Half of the respondents (50.0%) experienced a moderate workload, and 43.3% reported moderate job stress. Statistical analysis showed a significant relationship between workload and job stress among ER nurses (p = 0.001). Conclusion: Workload is significantly associated with job stress among ER nurses. Appropriate workload management strategies are needed to reduce occupational stress and support nurses' well-being and performance in emergency care settings. Keywords: Emergency Room; Job Stress; Nurses; Workload.